Efficiency of Water and Fertilizer Use in Agriculture: A Global Bibliometric Study - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study presents a comprehensive bibliometric analysis of global agricultural research on the efficiency of water and fertilizer use. As agricultural systems face increasing pressure to meet the growing global demand for food while minimizing environmental impacts, understanding the optimal use of water and fertilizers has become crucial. Through bibliometric techniques, this study analyzes key trends, influential publications, and research clusters that explore the intersection of water and fertilizer use efficiency, sustainable agriculture, and environmental concerns. The findings highlight the evolving nature of research, with significant contributions from major research hubs such as China, India, the United States, and Europe. Additionally, the study reveals the increasing importance of technological innovations and international collaboration in advancing sustainable agricultural practices. The research serves as a valuable resource for scholars and policymakers seeking to foster innovation and sustainability in the agricultural sector.